The Efficacy of a Plant Based Formulation in the Symptomatic Management of Mild COVID-19 Cases: A Double Blind, Randomized Controlled Trial - Das, Sanjib kumar; Dash, Durga Prasad; Panda, Pradip Kumar; Sadana, Sandhya; Kumar, Reddy M Ravi; K, Venkatesh Hari; Kanchibhotla, Divya (Archives of Clinical and Medical Case Reports, 2023)
Background: The COVID-19 pandemic has infected millions of people globally. There is a need for integrated modern and traditional systems of medicine to work together to find effective solutions quickly. Methods: NAOQ19 is a plant based formulation of 13 herbs. 50 COVID-19 patients were enrolled in the study. RT-PCR analysis was done on day 1, day 5 and day 10. Clinical symptoms were noted daily. Result: NAOQ19 arm showed a higher population with RT-PCR negative compared to the placebo arm on Day 5 (76% vs 0%) On Day 5, NAOQ19 arm showed a complete recovery from few symptoms while by Day 10, they showed complete recovery from all symptoms, unlike the placebo arm which showed only 10.5% of the population with clinical recovery on day 10. Conclusion: NAOQ19 facilitated a faster recovery from all clinical features of COVID-19, when compared to the placebo group. No side effects were observed during the entire study duration. CTRI Registration: CTRI/2021/08/036025